Latest Hydroforming Technology of Metallic Tubes and Sheets - Manabe, Ken-ichi; Hwang, Yeong-Maw (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue and Book, 'Latest Hydroforming Technology of Metallic Tubes and Sheets', includes 16 papers, which cover the state of the art of forming technologies in the relevant topics in the field. The technologies and methodologies presented in these papers will be very helpful for scientists, engineers, and technicians in product development or forming technology innovation related to tube hydroforming processes.